1989
DOI: 10.1128/iai.57.7.2230-2236.1989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional antigenic segments of toxic shock syndrome toxin 1 by differential immunoreactivity and by differential mitogenic responses of human peripheral blood mononuclear cells, using active toxin fragments

Abstract: When toxic shock syndrome toxin 1 was subjected to papain hydrolysis, two serologically active fragments of 16.3 kilodaltons (16K fragment) and 12.4 kilodaltons (12K fragment) were generated, whereas a third fragment of 9.7 kilodaltons (1OK fragment) was inactive. The biologic activities of the fragments were evaluated in vitro by determining their ability to promote nonspecific proliferation of human peripheral blood mononuclear cells. The 12K fragment was significantly (P c 0.013) more stimulatory than the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Blomster-Hautamaa et al (4), Murphy et al (25), and Kokan-Moore and Bergdoll (17) showed that an internal cyanogen bromide fragment (amino acids 34 to 158) retained mitogenic activity and immunological reactivity to anti-TSST-1 MAbs. Edwin and Kass (13) showed that a papain fragment of TSST-1 corresponding to its carboxy terminus (amino acids 88 to 194) retained biological activities as well as reactivity with several anti-TSST-1 MAbs developed in our laboratory (7). On the basis of these observations, they postulated that the biologically active region of TSST-1 resides in a 71-amino-acid segment encompassed by residues 88 and 158.…”
Section: Discussionmentioning
confidence: 96%
“…Blomster-Hautamaa et al (4), Murphy et al (25), and Kokan-Moore and Bergdoll (17) showed that an internal cyanogen bromide fragment (amino acids 34 to 158) retained mitogenic activity and immunological reactivity to anti-TSST-1 MAbs. Edwin and Kass (13) showed that a papain fragment of TSST-1 corresponding to its carboxy terminus (amino acids 88 to 194) retained biological activities as well as reactivity with several anti-TSST-1 MAbs developed in our laboratory (7). On the basis of these observations, they postulated that the biologically active region of TSST-1 resides in a 71-amino-acid segment encompassed by residues 88 and 158.…”
Section: Discussionmentioning
confidence: 96%
“…Historically, empirical epitope localization of protein antigens has relied upon either enzymatic digestion or cyanogen bromide cleavage into successively smaller fragments retaining epitopic specificity (12). Later, advances in peptide synthesis technology paved the way for the generation of small fragments with overlapping sequences and the construction of synthetic peptides corresponding to different areas of the protein, which could be probed for reactivity with T or B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have thoroughly investigated residues within superantigens, TCR, and class II molecules that are important for their physical and functional interaction (5,10,22,23,30,41,42,65,101,107,112,113,117,126,202,205,206,213,235,254,257,275). Studies investigating functional domains of the staphylococcal enterotoxin (SE) superantigens have localized mitogenically important regions to the amino-terminal part of the molecule (30,126,203), while others have suggested the importance of residues at the carboxy-terminal half (24,113).…”
Section: Functional Domains Within the Pyrogenic Superantigens Importmentioning
confidence: 99%